Comparative Morphometrics Based On Discriminant Analysis in Rooster and Hen of Local Chicken East Kalimantan - S. N., Rahmatullah; Efendi, Z.; Mayulu, H.; Ardhani, F.; Sulaiman, A. (Jurnal Peternakan Tropika, 2018)
The local chicken East Kalimantan ( Nunukan chicken crossbreed ) is one of the chickens crossing from Nunukan chicken and local chicken of East Kalimantan as one of genetic resources of genuine chicken from Borneo which has the potential to be a chicken breeding in Indonesia. This chicken is a native chicken Indonesia that has a different phenotypic diversity of other local chickens. The aim at the study was to compare and study chicken differentiation variables based on the size of rooster and hen’s local chickens of based on discriminant analysis approach. Phenotypic characteristics of body size used as the basis of characterization is body weight (BW), Height of Body (HB), Body length (BL), chest circumference (CC), chest width (CW) and shank length (SL).   The research was carried out at the House’s of Local Chicken Maintenance have Agriculture, Fisheries and Forestry Office of Samarinda City Government, East Kalimantan.  The material used 35 local chickens East Kalimantan consists of 21 rooster and 14 hens chicken. Six measured body size variables were body weight, height weight, body length, chest circumference, chest width and shank length.  Statistical analysis using descriptive analysis and discriminant analysis with the help of statistical programme computer to find out the differentiation variables between rooster’s and hens chickens were observed. The results showed that significant body size variables differed from height of body and shank length except body length, chest circumference, and chest width. The variability of morphometrics of local chickens of East Kalimantan was 64.16%, while the discriminant model formed for body weight into this study on local chickens of East Kalimantan was Y = 0.649 - 0.359HB + 1.144SL.   Keywords : morphometrics, discriminant analysis, local chicken, east Kalimantan.